RETENSI PEMAHAMAN ANATOMI MAHASISWA ANGKATAN 2023 FAKULTAS KEDOKTERAN BAITURRAHMAH TERHADAP OPTIMALISASI ANATOMAGE TABLE DALAM CAPAIAN KOGNITIF - Insil Pendri Hariyani; Aisyah Az Zahra; Naima Lassie (Yayasan Nusantara Hasana Berdikari, 2025)
Anatomy comprehension is a fundamental component in medical education. Alongside technological developments, innovative learning tools such as the Anatomage Table have been introduced to enhance anatomical visualization skills. This study aimed to evaluate the effectiveness of Anatomage Table compared to conventional methods in improving students' anatomical understanding. This quantitative comparative study involved 64 medical students at the Faculty of Medicine, Universitas Baiturrahmah. Participants were divided into two groups: the Anatomage Table group and the conventional learning group. Pre-test and post-test assessments were used, and data were analyzed using paired t-test and independent t-test. Both groups showed significant improvements in post-test scores (p < 0.001). The Anatomage Table group had a higher mean increase; however, the difference between groups was not statistically significant (p = 0.348). The Anatomage Table effectively improves students' understanding of anatomy but does not show significant superiority over conventional methods. A blended approach may provide optimal educational outcomes.